Effects of Oleacein on High-Fat Diet-Dependent Steatosis, Weight Gain, and Insulin Resistance in Mice - Lombardo, Giovanni Enrico; Lepore, Saverio Massimo; Morittu, Valeria Maria; Arcidiacono, Biagio; Colica, Carmela; Procopio, Antonio; Maggisano, Valentina; Bulotta, Stefania; Costa, Nicola; Mignogna, Chiara; Britti, Domenico; Brunetti, Antonio; et al. (Frontiers in Endocrinology, 2018)
Many reports indicate that the protective action of nutraceuticals in the Mediterranean diet, against metabolic and cardiovascular diseases, can be attributed to the action of polyphenolic components of extra-virgin olive oil (EVOO). Here, we evaluated the protective effects of oleacein, one of the most abundant secoiridoids in EVOO, on the damages/metabolic alterations caused by high-fat diet (HFD) in male C57BL/6JolaHsd mice. After 5 weeks of treatment with 20 mg/kg of oleacein, body weight, glycemia, insulinemia, serum lipids, and histologic examination of liver tissue indicated a protective action of oleacein against abdominal fat accumulation, weight gain, and liver steatosis, with improvement of insulin-dependent glucose and lipid metabolism. Both serum parameters and hepatic histologic examination were altered in mice fed with HFD. By contrast, in the animals that received oleacein, plasma glucose, cholesterol and triglyceride serum levels, and liver histology were similar to controls fed with normocaloric diet. In addition, protein levels of FAS, SREBP-1, and phospho-ERK in liver were positively modulated by oleacein, indicating an improvement in liver insulin sensitivity. In a group of obese mice, treatment with oleacein determined a light, but still significant reduction of the increase in body weight, mainly due to lesser liver steatosis enlargement, associated with reduced levels of SREBP-1 and phospho-ERK and lower levels of total serum cholesterol; in these animals, altered plasma glucose and triglyceride serum levels were not reverted by oleacein. These results indicate that HFD-related hepatic insulin resistance may be partially prevented by oral administration of oleacein, suggesting a protective role of this nutraceutical against diet-dependent metabolic alterations. Additional studies are necessary to check whether oleacein can be used as an adjuvant to improve insulin sensitivity in humans.